Đánh giá tính bền vững của nợ công Việt Nam theo mô hình DSF của Quỹ Tiền tệ Quốc tế và Ngân hàng Thế giới - Nguyen Thi, Lan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This study aims to give an overall assessment on public debt of Vietnam in the period of 2011–2016. Adopting debt sustainability framework (DSF) of the World Bank (WB) and International Monetary Fund (IMF), the paper evaluates the sustainability of public debt in Vietnam, and on that basis proposes some solutions to improve the sustainability of public debt in Vietnam in the near future. The research results show that although Vietnam's current public debt rate (64.73% of GDP) is below the threshold prescribed by the National Assembly, it, if assessed under DSF, is highly risky and unsustainable as there are two indicators exceeding the warning threshold of DSF (2012) of IMF and WB.
Keywords: Public Debt; Public Debt Sustainability; Debt Sustainability Framework (DSF)